Fostering Professional Ethical Competence During Teacher Training Practice - Pérez-García, María Purificación; Latorre-Medina, María José; Blanco-Encomienda, Francisco Javier (Pedagogika, 2015)
Professionals who have undergone their training at university should possess not only the knowledge-base necessary to practice in their chosen profession, but also the ethical principles that ensure responsible professional practice and the corresponding benefits for society. The research project addressed in the present article aimed to contribute to fostering ethical competence and commitment amongst future teachers. During the experience the participants had the opportunity to design tasks that stimulated reflection, critique and ethical awareness.